Konsep Kewajiban Dalam Hukum Perikatan: Teori dan Penerapannya Dalam Hukum Kontrak - Stevani, Frisca Adelia; Silalahi, Riovaldi Paruntungan; Pridehan, Syahla; Maharani, Velissa; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to examine the concept of obligation in the law of engagement as regulated in the Civil Code (KUHPerdata) and how the basic theories of obligation are applied in the practice of contract law in Indonesia. This research uses a normative legal method with a statutory and doctrinal approach, as well as analyzing court decisions related to bonds and contracts. Obligations in contract law include various types, namely primary obligations, additional obligations, conditional obligations, alternative obligations, and undivided obligations. In addition, this research also explores the forms of default that commonly occur in binding relationships, such as inability to fulfill obligations, delays, or violations of the substance of the contract, as well as default resolution mechanisms applied in the practice of contract law in Indonesia. The focus of this research is to provide an integrated analysis of how theories of liability can be implemented effectively and fairly in the context of civil law. The results of the research are expected to provide a comprehensive guide for academics, legal practitioners, and the general public to understand the application of liability theories in engagement and default resolution in Indonesia.